A De Novo Mutation in COL1A1 in a Holstein Calf with Osteogenesis Imperfecta Type II - Joana G. P. Jacinto; Irene M. Häfliger; Fintan J. McEvoy; Cord Drögemüller; Jørgen S. Agerholm (Animals, 2021)
Osteogenesis imperfecta (OI) type II is a genetic connective tissue disorder characterized by bone fragility, severe skeletal deformities and shortened limbs. OI usually causes perinatal death of affected individuals. OI type II diagnosis in humans is established by the identification of heterozygous mutations in genes coding for collagens. The purpose of this study was to characterize the pathological phenotype of an OI type II-affected neonatal Holstein calf and to identify the causative genetic variant by whole-genome sequencing (WGS). The calf had acute as well as intrauterine fractures, abnormally shaped long bones and localized arthrogryposis. Genetic analysis revealed a private heterozygous missense variant in COL1A1 (c.3917T>A) located in the fibrillar collagen NC1 domain (p.Val1306Glu) that most likely occurred de novo. This confirmed the diagnosis of OI type II and represents the first report of a pathogenic variant in the fibrillar collagen NC domain of COL1A1 associated to OI type II in domestic animals. Furthermore, this study highlights the utility of WGS-based precise diagnostics for understanding congenital disorders in cattle and the need for continued surveillance for rare lethal genetic disorders in cattle.